Bicarbonate-rich wastewater as a carbon fertilizer for culture of Dictyosphaerium sp. of a giant pyrenoid. (20th November 2018) - Qilu, Cheng; Ligen, Xu; Fangmin, Cheng; Gang, Pan; Qifa, Zhou
Abstract: Microalgae require a large amount of carbon (C) fertilizer for efficient biomass production. We explored the feasibility of using bicarbonate-rich wastewater as a carbon fertilizer for algal cultures and characterized the morphological and physiological features of C-deficient Dictyosphaerium sp. algae. Addition of bicarbonate-rich wastewater to media increased peak algal biomass by more than four-fold, and removal of the bicarbonate from the wastewater decreased the peak algal biomass by more than 3 times, and both the algal biomass productivity and the bicarbonate depletion rate were positively and significantly (P < 0.01) related to the bicarbonate level. We observed a giant pyrenoid in Dictyosphaerium cells. Consistently, this species exhibited an exceptionally high CO2 enrichment and the expression level of limiting CO2 inducible protein gene was extremely high. The disruption in structural integrity was evident in the algae cultured under 0.4 g/L of bicarbonate. Transcript profiling accurately revealed the C and N status in the algae. Our results indicate that the bicarbonate-rich and Na-low wastewater could provide adequate and excellent C source for algal growth. Highlights: The bicarbonate-rich and Na-low wastewater could be used as an excellent C fertilizer in algal production. Dictyosphaerium sp. of a giant pyrenoid exhibited an exceptionally high CO2 enrichment. Transcript profiling could accurately reveal the C and N status in the algae.